The influence of endodontic treatment on blood pressure reduction in patients with vital irreversible pulpitis - Hussein HM; Raafat AS; Amory ZS; AL-Juboori MJ (Dove Medical Press, 2019)
Hashim M Hussein, Ahmed S Raafat, Zainab S Amory, Mohammed Jasim AL-JubooriDepartment of Dentistry, Al-Rafidain University-College, Baghdad, IraqBackground: During endodontic treatment, endodontists must be aware of the various factors that may decrease or increase blood pressure. This study aimed to assess the mean percentages of systolic, diastolic, and arterial blood pressure (MSBP, MDAP, MABP) reduction in patients with vital irreversible pulpitis in teeth and who were treated at three visits to endodontists in three age groups (20–34 years, 35–50 years, 51–65 years).Materials and methods: A total of 100 teeth with vital irreversible pulpitis from 100 patients were included. All patients underwent 3 visits for endodontic treatment. The 1st visit included removal of vital pulp tissue and a determination of working length, the 2nd visit included canal preparation and widening, and at the 3rd visit the canal was obturated and sealed by gutta percha and sealer. Blood pressure for all patients was checked and documented once before starting treatment and three times during treatment at different intervals during all visits.Results: There were significantly higher percentage reductions in MSBP, MDBP, and MABP at the 1st visit for endodontic treatment in comparison to other visits (2nd and 3rd) for all patients. Additionally, there were significantly higher percentage reductions in MSBP, MDBP, and MABP at the 1st visit for endodontic treatment in comparison to other visits in males and females, for all age groups, both anesthesia injection-type groups (infiltration and block), and all treated tooth types except mandibular anterior teeth, and there were nonsignificant differences among groups. However, there were nonsignificant differences in MSBP, MDBP, and MABP between males and females, between infiltration and block injection groups and in relation to teeth types at all visits.Conclusions: The reduction of blood pressure in patients undergoing endodontic treatment of vital teeth with irreversible pulpits is common, especially at the 1st visit for pulp extirpation.Keywords: irreversible pulpitis, endodontic treatment, vital teeth, anesthesia, age, gender